2007
DOI: 10.1002/polb.21330
|View full text |Cite
|
Sign up to set email alerts
|

Shape instabilities in adsorbed polymer condensates

Abstract: A polymer chain in a poor solvent collapses to a spherical globule. If this globule is subsequently deformed, either by stretching it or if it has some non-zero net electric charge, it will become unstable to sinusoidal perturbations leading to novel final states. When such globules are imaged by direct methods such as atomic force microscopy the substrate on which they adsorb can affect the final morphological state. We therefore investigate strongly adsorbed polymers in poor solvents. We demonstrate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Consequently, the conformation of PEs is a result of the competition between the attractive interaction and the electrostatic repulsion. A large number of theoretical and simulation studies have focused on this topic . It has been shown that the pearl‐necklace conformation, which comprises compact beads connected by narrow strings, is a possible state of PEs in poor solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the conformation of PEs is a result of the competition between the attractive interaction and the electrostatic repulsion. A large number of theoretical and simulation studies have focused on this topic . It has been shown that the pearl‐necklace conformation, which comprises compact beads connected by narrow strings, is a possible state of PEs in poor solvents.…”
Section: Introductionmentioning
confidence: 99%